RIG-I Signaling via MAVS Is Dispensable for Survival in Lethal Influenza Infection In Vivo - Wu, Wenxin; Wang, Xiaoqiu; Zhang, Wei; Tian, Lili; Booth, J. Leland; Duggan, Elizabeth S.; More, Sunil; Liu, Lin; Dozmorov, Mikhail; Metcalf, Jordan P. (Mediators of Inflammation, 2018)
Retinoic acid-inducible gene I (RIG-I) is an important regulator of virus-induced antiviral interferons (IFNs) and proinflammatory cytokines. It requires interaction with an adaptor molecule, mitochondrial antiviral-signaling protein (MAVS), to activate downstream signaling pathways. To elucidate the mechanism(s) by which RIG-I-dependent recognition of IAV infection in vivo triggers innate immune responses, we infected mutant mice lacking RIG-I or MAVS with influenza A virus (IAV) and measured their innate immune responses. As has previously been demonstrated with isolated deletion of the virus recognition receptors TLR3, TLR7, and NOD2, RIG-I or MAVS knockout (KO) did not result in higher mortality and did not reduce IAV-induced cytokine responses in mice. Infected RIG-I KO animals displayed similar lung inflammation profiles as did WT mice, in terms of the protein concentration, total cell count, and inflammatory cell composition in the bronchoalveolar lavage fluid. RNA-Seq results demonstrated that all types of mice exhibited equivalent antiviral and inflammatory gene responses following IAV infection. Together, the results indicated that although RIG-I is important in innate cytokine responses in vitro, individual deletion of the genes encoding RIG-I or MAVS did not change survival or innate responses in vivo after IAV infection in mice.